Pedoman Tatalaksana Takiaritmia Supraventrikular (TaSuV) - Raharjo, Sunu Budhi; Yuniadi, Yoga; Muzakkir, Muzakkir; Yansen, Ignatius; Munawar, Dian Andina; Hermanto, Dony Yugo (The Indonesian Heart Association, 2017)
No abstract